Evaluation of urinary and serum level of chemokine (C‐C motif) ligand 2 as a potential biomarker in canine urothelial tumours. (26th December 2018) - Shimizu, N.; Hamaide, A.; Dourcy, M.; Noël, S.; Clercx, C.; Teske, E.
Abstract : Chemokine (C‐C motif) ligand 2 (CCL2) is a chemotactic cytokine recruiting monocytes, releasing growth factors and promoting adhesion in vascular endothelium. Elevated serum and urinary CCL2 levels and expression of its receptor (CCR2) have been associated with tumorigenesis in human urinary malignancies. CCL2 implication has not been investigated in canine urothelial carcinoma. The aim of this study was to evaluate CCL2 serum and urine levels (measured by ELISA) in dogs with urothelial carcinoma or non‐neoplastic urinary tract disease. CCL2 serum and urine levels were significantly higher in diseased dogs compared with healthy dogs ( P < 0.001). Dogs with carcinoma had significantly higher serum and urine CCL2 levels ( P = 0.001) than healthy dogs. Dogs with metastases showed significantly lower serum and urine CCL2 levels compared with the non‐metastasised tumour group ( P = 0.007). CCL2 as a diagnostic marker for urothelial carcinoma held a sensitivity of 95.2% and a specificity of 38.2% in the urine. As a staging marker, sensitivity was 85.7% and specificity was 57.1% with a positive predictive value of 75.7% and a negative predictive value of 71.9%. Further investigation is needed to define the role of CCL2 as a prognostic marker in canine urothelial carcinoma.